SEPSIS-3: UPDATED MAIN DEFINITIONS, POTENTIAL PROBLEMS AND NEXT PRACTICAL STEPS - V. A. Rudnov; V. V. Kulabukhov (Вестник анестезиологии и реаниматологии, 2018)
Goal: to review new definitions and criteria of sepsis and septic shock by Society Critical Care Medicine (SCCM) and European Society Intensive Care Medicine (ESICM) in the light of evolving understanding of interaction between the contagium and the host, appearance of potential problems and possible clinical benefits for the practice. Results. Upon results of the review the conclusion has been made that the sepsis is to be considered not only as progressing system inflammation but given the diversity of the response – as life threatening regulation disorder of the host reaction (disregulation) to the infection with acute multi-organ dysfunction reflecting the tissue damage of the host. SOFA score is to be used as a diagnostic tool. The introduction of the new concept into routine practice is limited since it can be difficult to define the contribution of the infection into already existing dysfunction due to the presence of some chronic disorder, since doctors do not adhere to using scales of multi-organic failure severity and it is impossible to test blood lactate in numerous medical units. Introduction of new criteria into practice can be beneficial for the justification of the care provision in hospital due to the risk of the unfavorable outcome and with the purpose of targeted monitoring. Quick SOFA is to be used to detect patients with the suspicion of sepsis and developing life threatening conditions beyond premises the intensive care departments.